2020
DOI: 10.1289/ehp4817
|View full text |Cite
|
Sign up to set email alerts
|

Privacy Risks of Sharing Data from Environmental Health Studies

Abstract: BACKGROUND: Sharing research data uses resources effectively; enables large, diverse data sets; and supports rigor and reproducibility. However, sharing such data increases privacy risks for participants who may be re-identified by linking study data to outside data sets. These risks have been investigated for genetic and medical records but rarely for environmental data. OBJECTIVES: We evaluated how data in environmental health (EH) studies may be vulnerable to linkage and we investigated, in a case study, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…We have implemented PeQES using the Rust-based Fortanix Enclave Development Platform 3 . The prototype implementation of the PeQES platform is available under an open source license 4 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have implemented PeQES using the Rust-based Fortanix Enclave Development Platform 3 . The prototype implementation of the PeQES platform is available under an open source license 4 .…”
Section: Methodsmentioning
confidence: 99%
“…This practice is sometimes complemented with the publication of primary data sets to verify analyses and to foster reuse [13]. This practice yields new privacy issues [3], though (e.g., de-anonymization and re-identification attacks against study participants).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in conjunction with existing data sets such as tax and real estate data or voter lists, new volunteer-collected data sets may enable re-identification of individuals or their locations via data triangulation (Golle, 2006). Even when researchers anonymize environmental health data by removing overt identifiers such as names and addresses, risks to re-identification of participants remain (Boronow et al, 2020).…”
Section: Data Confidentialitymentioning
confidence: 99%
“…Researchers have shown that robust de-anonymization is possible in many domains, such as social networks (Narayanan, Shi, & Rubinstein, 2011;Narayanan & Shmatikov, 2009), participants in social media studies (Ayers, Caputi, Nebeker, & Dredze, 2018), genetic data (Craig, 2016;Ellenbogen & Narayanan, 2019;Erlich, Shor, Peer, & Carmi, 2018;Gymrek, McGuire, Golan, Halperin, & Erlich, 2013;Homer et al, 2008), environmental health studies (Boronow et al, 2020), location data (De Montjoye, Hidalgo, Verleysen, & Blondel, 2013Golle & Partridge, 2009;Zang & Bolot, 2011), browsing histories (Su, Shukla, Goel, & Narayanan, 2017), and even writing style (Narayanan et al, 2012). The key finding of all this research, including theoretical evidence (Datta, Sharma, & Sinha, 2012), is that high-dimensional data is inherently vulnerable to deanonymization.…”
Section: De-anonymization Attacks On Data Setsmentioning
confidence: 99%